1990
DOI: 10.1055/s-2008-1042586
|View full text |Cite
|
Sign up to set email alerts
|

Air Reduction for Intussusception in Infancy and Childhood:Ultrasonographic Diagnosis and Management Without X-Ray Exposure

Abstract: For the treatment of uncomplicated intussusception in infants and children, we attempted air reduction without x-ray study to avoid the genetic and carcinogenic effects of radiation. Intussusception could generally be diagnosed by ultrasonography in addition to the history and typical clinical signs without using a barium enema. The success of reduction could also be safely evaluated from the disappearance of both the characteristic sonographic target sign and the abdominal palpable mass, and improvement in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 9 publications
1
14
0
1
Order By: Relevance
“…Studies from Asia used the combination of US and rectally applied pneumatic reduction with a success rate of up to 95%, and recent studies demonstrated no higher rates of complications compared to other previously published techniques [67][68][69][70]. However, this method still failed to gain widespread support.…”
Section: Reduction Techniquesmentioning
confidence: 89%
“…Studies from Asia used the combination of US and rectally applied pneumatic reduction with a success rate of up to 95%, and recent studies demonstrated no higher rates of complications compared to other previously published techniques [67][68][69][70]. However, this method still failed to gain widespread support.…”
Section: Reduction Techniquesmentioning
confidence: 89%
“…There are many reports of enema reduction under sonography 76,86–97 since Bolia's report 98 in 1985. The greatest advantage of sonography is that it does not involve radiation exposure to children, and therefore reduction can be attempted repeatedly without concern for time 76 (level 4).…”
Section: Treatmentmentioning
confidence: 99%
“…This has caused some controversy and some criticism in the literature [1][2][3]5]. Indeed, successful management can be achieved in one of a number of different ways [1][2][3][5][6][7][8][9][10][11][12][13][14][15]. In future years, the management of intussusception will probably continue to evolve.…”
Section: Ileocolic and Ileo-ileocolic Intussusceptionmentioning
confidence: 99%
“…There are many series in the recent literature that have shown a reduction rate of intussusception varying from 80% to as high as 95% [2,[12][13][14][15]. These series have used either fluoroscopic or sonographic guidance for reducing the intussusception and the series have used either hydrostatic [barium, water soluble contrast, saline] or pneumatic reduction (Fig.…”
Section: Reductionmentioning
confidence: 99%